Risk factors and background diseases in different variants of ischemic stroke in the elderly and senile age - Asadullaev Maksud; Vakhabova Nargiza; Asadullaev Hamidjon (International Journal on Orange Technologies, 2020)
Gender differences in risk factors and background diseases in elderly and senile individuals with ischemic stroke were established. Thus, it was found that senile individuals showed a decrease in the proportion of hemodynamic and lacunar stroke due to an increase in the percentage of patients with atherothrombotic stroke among both women and men. Risk factors for ischemic stroke also had their own characteristics and differed depending on age and gender. Taking into account the heterogeneity of stroke in individuals aged 44-59 years, the highest percentage (p<0.05) of Smoking, dyslipidemia (P<0.05), and psych emotional stress (p<0.05) was revealed. In elderly and senile patients, the Smoking factor significantly decreases (P<0.05). In individuals aged 44-59 years, there was a significant prevalence of atherosclerosis, arterial hypertension, CHD, TIA, rheumatism in men (p<0.05), and diabetes mellitus and heart rhythm disorders in women (p<0.05). At the same time, the prevalence of the specific weight of CHD and TIA in the structure of background diseases remained in elderly men (p<0.05).